2014
DOI: 10.1007/s00221-014-4125-4
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon vibration-induced changes in plantar flexor corticospinal excitability

Abstract: Daily Achilles tendon vibration has been shown to increase muscle force, likely via corticospinal neural adaptations. The aim of the present study was to determine the extent by which corticospinal excitability is influenced during direct Achilles tendon vibration. Motor-evoked potentials (MEPs) were elicited in the soleus (SOL), gastrocnemius medialis (GM) and tibialis anterior (TA) by transcranial magnetic stimulation of the motor cortical area of the leg with and without Achilles tendon vibration at various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 39 publications
5
18
1
Order By: Relevance
“…This increase in corticospinal excitability is in agreement with our previous study (Lapole et al 2015) and is strengthened by vMT being 12 % lower than rMT. A similar result has previously been reported during Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This increase in corticospinal excitability is in agreement with our previous study (Lapole et al 2015) and is strengthened by vMT being 12 % lower than rMT. A similar result has previously been reported during Fig.…”
Section: Discussionsupporting
confidence: 92%
“…For each trial of 10 TMS pulses, the three largest responses were averaged to reduce intrasubject variability within each trial. As in our previous studies (Lapole et al 2012(Lapole et al , 2015, we observed that such analysis did not alter the magnitude of the reported vibration-induced changes.…”
Section: Experimental Protocolsupporting
confidence: 46%
See 3 more Smart Citations